Proanthocyanidins induce analgesic and anxiolytic effects in spared nerve injured mice by decreasing in vivo firing rate of pyramidal cells in the insular cortex - Wang, Pan; Si, Hua-Xing; Zhu, Da-Yu; Xing, Ke-Ke; Wang, Jian; Cao, Ting-Ting; Zhao, Han; Liu, Xiao-Die; Zhang, Ming-Ming; Chen, Tao (Frontiers in Molecular Neuroscience, 2023)
Neuropathic pain is one of the most common symptoms of clinical pain that often accompanied by severe emotional changes such as anxiety. However, the treatment for comorbidity of chronic pain and anxiety is limited. Proanthocyanidins (PACs), a group of polyphenols enriched in plants and foods, have been reported to cause pain-alleviating effects. However, whether and how PACs induce analgesic and anxiolytic effects in the central nervous system remain obscure. In the present study, we observed that microinjection of PACs into the insular cortex (IC) inhibited mechanical and spontaneous pain sensitivity and anxiety-like behaviors in mice with spared nerve injury. Meanwhile, PACs application exclusively reduced the FOS expression in the pyramidal cells but not interneurons in the IC. In vivo electrophysiological recording of the IC further showed that PACS application inhibited the firing rate of spikes of pyramidal cells of IC in neuropathic pain mice. In summary, PACs induce analgesic and anxiolytic effects by inhibiting the spiking of pyramidal cells of the IC in mice with neuropathic pain, which should provide new evidence of PACs as the potential clinical treatment of chronic pain and anxiety comorbidity.